Tagzeitentexte des Mittelalters Untersuchungen und Texte zur deutschen Gebetbuchliteratur - Matter, Stefan (Liturgie und Volkssprache, 2021)
"Tagzeitentexte" are texts structured according to the prayer schedules used by clergy for daily services. They provide special insight into the structure and usage of medieval prayer-books, given their prominence as one of the largest groups of texts. For the first time, this study provides a scholarly survey of these diverse texts.